Analisis Psikologis Tokoh dalam Novel Sepotong Senja Untuk Pacarku: Trilogi Alina Karya Seno Gumira Ajidarma - M Ghufroni An'ars; Nalan Meilia Sisi (BADAN PENERBIT STIEPARI PRESS, 2024)
Psychoanalytic analysis of the characters in Seno Gumira Ajidarma’s novel “Sepotong Senja untuk Pacarku: Trilogi Alina” and their harmony with social reality using Sigmund Freud’s psychological studies. Objective: The purpose of this research is to describe the character traits of the figures in Seno Gumira Ajidarma’s novel “Sepotong Senja untuk Pacarku: Trilogi Alina” using Sigmund Freud’s psychological perspective. Method: A psychoanalytic analysis of the characters in the novel “Sepotong Senja untuk Pacarku: Trilogi Alina” by Seno Gumira Ajidarma and their harmony with social reality using qualitative descriptive methods and Sigmund Freud’s psychological perspective. Findings: The research findings indicate that there are 8 data points on the characters Sukab and the Postman that align with males in social reality, while for the character Alina, there are 5 data points, 3 of which are in harmony, but 2 of which are not in harmony with females in social reality. Conclusion: The psychological harmony of the characters in Seno Gumira Ajidarma’s novel “Sepotong Senja untuk Pacarku: Trilogi Alina” can be a benchmark indicating that the author reflects society in the characters written in his work.